2013
DOI: 10.1073/pnas.1310365110
|View full text |Cite
|
Sign up to set email alerts
|

Implications for the evolution of eukaryotic amino-terminal acetyltransferase (NAT) enzymes from the structure of an archaeal ortholog

Abstract: Amino-terminal acetylation is a ubiquitous modification in eukaryotes that is involved in a growing number of biological processes. There are six known eukaryotic amino-terminal acetyltransferases (NATs), which are differentiated from one another on the basis of substrate specificity. To date, two eukaryotic NATs, NatA and NatE, have been structurally characterized, of which NatA will acetylate the α-amino group of a number of nonmethionine amino-terminal residue substrates such as serine; NatE requires a subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 25 publications
5
40
0
Order By: Relevance
“…In line with this, in vitro acetylation assays showed that, although ssNaa10 has higher sequence similarity to hNaa10 over hNaa50 (34% vs. 24% sequence identity, respectively) and therefore has a preference for Ser- over Met-amino-terminal substrates, it is still able to accommodate NatA and NatE substrates (Liszczak and Marmorstein, 2013). Furthermore, studies on the X-ray crystal structure of ssNaa10 combined with mutagenesis and kinetic analyses showed that the active site of ssNaa10 represents a hybrid of the NatA and NatE active sites (Liszczak and Marmorstein, 2013), explaining the above findings. A later study confirmed these findings and showed that Glu35 has a critical role for the unique substrate specificity of ssNaa10 (Chang and Hsu, 2015).…”
Section: Nata In Other Organismsmentioning
confidence: 76%
See 1 more Smart Citation
“…In line with this, in vitro acetylation assays showed that, although ssNaa10 has higher sequence similarity to hNaa10 over hNaa50 (34% vs. 24% sequence identity, respectively) and therefore has a preference for Ser- over Met-amino-terminal substrates, it is still able to accommodate NatA and NatE substrates (Liszczak and Marmorstein, 2013). Furthermore, studies on the X-ray crystal structure of ssNaa10 combined with mutagenesis and kinetic analyses showed that the active site of ssNaa10 represents a hybrid of the NatA and NatE active sites (Liszczak and Marmorstein, 2013), explaining the above findings. A later study confirmed these findings and showed that Glu35 has a critical role for the unique substrate specificity of ssNaa10 (Chang and Hsu, 2015).…”
Section: Nata In Other Organismsmentioning
confidence: 76%
“…In the archeae Sulfolobus solfataricus , only a single ssNaa10 has been identified to date with a more relaxed substrate specificity (acetylating NatA, NatB and NatC-type substrates) (Mackay et al, 2007). A recent structural comparison of ssNaa10 with S. pombe Naa10 showed that the active site of ssNaa10 represents a hybrid of Naa10 and Naa50 and, as a result, can facilitate acetylation of Met- and non-Met-containing amino-terminal substrate peptides (Liszczak and Marmorstein, 2013). Therefore, the authors suggest that this ssNaa10 is an ancestral NAT variant from which the eukaryotic NAT machinery evolved (Liszczak and Marmorstein, 2013).…”
Section: Nata In Other Organismsmentioning
confidence: 99%
“…These include the transcription factor Runt-related transcription factor 2 (Runx2) (11), the enzyme methionine sulfoxide reductase A (MSRA) (12), and myosin light chain kinase (MLCK) (13). These findings were surprising to us because the structures of all NATs determined to date (9, 14 -17), including Naa10 (9), contain an extended loop that seems to occlude lysine side chains within a polypeptide from lying across the active site as they do in KATs (15)(16)(17)(18). In addition, other reports demonstrating that Naa10 acetylates a lysine residue on Hif-1␣ have failed to be replicated (19 -21), making the question of whether Naa10 is able to acetylate lysine residues controversial.…”
mentioning
confidence: 99%
“…Recently, the first structures of NATs and a NAT-complex were solved, providing a molecular understanding of the sequence specific Nt-acetylation of protein N termini (27)(28)(29)(30). Structural analyses of noncomplexed Naa10 and NatA from Schizosaccharomyces pombe reveal an allosteric modulator function of Naa15 in steering Naa10 specificity and provide a rational for the distinctive substrate specificity profiles observed when assaying non-complexed versus complexed Naa10 (10,27), with both forms co-existing in cells (10).…”
mentioning
confidence: 99%